2019
DOI: 10.1016/j.infbeh.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mother–infant interactions with firstborns and secondborns: A within-family study of European Americans

Abstract: Given the large numbers of families with more than one child, understanding similarities and differences in siblings' behaviors and in parents' interactions with their sibling infants is an important goal for advancing more representative developmental science. This study employed a within-family design to examine mean-level consistency and individual-order agreement in 5month-old sibling behaviors and maternal parenting practices with their firstborns and secondborns (ns=61 mothers and 122 infants). Each infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Our study also found that the association between the experience of COVID-19 and the risk of neurodevelopmental delay in specific domains among 1-year-olds only existed in firstborn children, which seems inconsistent with previous evidence. It has been shown that first-born children tend to be more intelligent and receive more language interactions from their parents than later-born children (43,44). There might be two reasons for this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also found that the association between the experience of COVID-19 and the risk of neurodevelopmental delay in specific domains among 1-year-olds only existed in firstborn children, which seems inconsistent with previous evidence. It has been shown that first-born children tend to be more intelligent and receive more language interactions from their parents than later-born children (43,44). There might be two reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…First, our findings suggest that the experience of the COVID-19 pandemic might potentially have a negative impact on child neurodevelopment in specific domains at specific ages, which raise concerns about the development of young children under the COVID-19 pandemic. Parents need to pay more attention to their children's development and adjust their rearing patterns at this special time (44). Second, given the absence of an association with "poor neurodevelopmental outcome, " this potential negative impact seemed to affect only a limited number of domains and have minor influences on the overall developmental outcome of the children.…”
Section: Discussionmentioning
confidence: 99%
“…If maternal stress is not a reason for the negative effect of older siblings on language development, this leaves open one other proposed route: That parents are more occupied with the older sibling at the expense of providing high-quality input to younger siblings (despite not being emotionally occupied with the burden of also having an older child). In other words, this is a mere matter of allocation of time, or a differential treatment of the two children (e.g., Bornstein et al, 2019). Indeed, it was previously shown, in US families, that when both siblings are present, parents may be more responsive to the older child, at the expense of providing (quality) language input to the younger child (Huttenlocher, Vasilyeva, Waterfall, Vevea, & Hedges, 2007; see also Hoff-Ginsberg & Krueger, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of Birth order, the study has shown that parents of children with chronic illness bear higher stress level compared to other parents, and in particular, a high Birth order in a family with a child with the disease, implies parents with high or suspicious stress, whereas a low Birth order in a family predicts parents with normal stress levels. It has been recently shown that the mother first born interaction differs from the mother second born interaction in healthy children [20].…”
Section: Discussionmentioning
confidence: 99%